The need for improved Australian data on social determinants of health inequities - Freeman, Toby; Musolino, Connie; van Eyk, Helen; Tesfay, Fisaha H; Baum, Fran; Flavel, Joanne; McKee, Martin (My University, 2022)
The coronavirus disease 2019 (COVID-19) pandemic has shone a light on longstanding inequities in societies.1 Yet, too often, these inequities are effectively invisible,1 and we can only know if we are tackling them if we can measure them. A lack of appropriate data is an important reason why research that has helped our understanding of health inequities is unevenly distributed internationally, with much concentrated in Europe and North America. Although Australia has some leading global centres for population health research, a lack of appropriate data creates a barrier to undertaking such research here. However, the available evidence indicates that socio-economic health inequities have increased since the 1980s.2 A better understanding of what is happening is important for many reasons, not least the law of unintended consequences; policies designed to improve overall health can inadvertently widen health inequities.3 It is only by understanding the scale and nature of existing inequities and differential impacts of responses to them that we can assess the effect of policies and monitor progress.4 Improved data collection and analysis is the first essential step to building back fairer from the impacts of COVID-19.
The Medical Journal of Australia
Keywords: Disadvantage, adversity and resilience; Health and wellbeing